Islamic Group Lending and Financial Inclusion - Aam Slamet Rusydiana; Abrista Devi (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2016)
Based on measurements of several indicators including the level of community participation, community empowerment, repayment rate was good, cross reporting good, and the application of penalties in accordance with the applicable rules, the results show that with the program GLM people feel the difference in economic condition and social than before and after the program. This is a major discovery is valuable. The development strategy for the program GLM is divided into seven levels with the elements most important include: The need for equality of access to funds for all types of financial institutions, both banking and lending model-based group, the need to improve the quality of human resources as a pioneer of service models based lending group this, as well as the importance of financial inclusion in the entire financial systemDOI: 10.15408/sjie.v5i1.3128